2018
DOI: 10.1016/j.rgg.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic model of formation of carbonates and uranium mineral phases in lakes Namshi-Nur and Tsagan-Tyrm (Cisbaikalia)

Abstract: The Tazheran lakes are located compactly in the small Tazheran steppe area. Their bottom sediments are predominantly various calcite–dolomite carbonates, and their waters are rich in uranium. The studies have shown that the main process in these lakes is chemogenic carbonate precipitation with the participation of carbon dioxide formed through the bacterial destruction of organic matter. For thermodynamic modeling of the composition of bottom sediments, we chose two lakes with different basic parameters. Calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Hence, uranium-rich groundwaters are concentrated by evaporation and the U(VI) is chelated by CO 2− 3 to form the highly soluble UO 2 (CO 3 ) 4− 3 in water, which is the main cause of the enrichment of uranium content in lakes in northwestern Mongolia. Strakhovenko et al [27] showed that biogeochemical processes have an impact on the mobility of uranium species. Andersson et al, [28] showed that the behavior of colloids suspended phase and colloids are beneficial for the removal of U at very low salinities.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, uranium-rich groundwaters are concentrated by evaporation and the U(VI) is chelated by CO 2− 3 to form the highly soluble UO 2 (CO 3 ) 4− 3 in water, which is the main cause of the enrichment of uranium content in lakes in northwestern Mongolia. Strakhovenko et al [27] showed that biogeochemical processes have an impact on the mobility of uranium species. Andersson et al, [28] showed that the behavior of colloids suspended phase and colloids are beneficial for the removal of U at very low salinities.…”
Section: Introductionmentioning
confidence: 99%